Masters theses from a university medical college: Publication in indexed scientific journals - Dhaliwal, Upreet (Medknow Publications, 2010)
BACKGROUND: The thesis is an integral part of postgraduate medical education in India. Publication of the results of the thesis in an indexed journal is desirable; it validates the research and makes results available to researchers worldwide. AIMS: To determine publication rates in indexed journals, of works derived from theses, and factors affecting publication. SETTINGS AND DESIGN: Postgraduate theses submitted over a five-year period (2001-05) in a university medical college were analyzed in a retrospective, observational study. MATERIALS AND METHODS: Data retrieved included name and gender of postgraduate student, names, department and hierarchy of supervisor and co-supervisor(s), year submitted, study design, sample size, and statistically significant difference between groups. To determine subsequent publication in an indexed journal, Medline search was performed up to December 2007. STATISTICAL ANALYSIS: Chi square test was used to compare publication rates based on categorical variables; Student's t-test was used to compare differences based on continuous variables. RESULTS: One hundred and sixty theses were retrieved, forty-eight (30%) were published. Papers were published 8-74 (33.7 ± 17.33) months after thesis submission; the postgraduate student was first author in papers from 26 (54%) of the published theses. Gender of the student, department of origin, year of thesis submission, hierarchy of the supervisor, number and department of co-supervisors, and thesis characteristics did not influence publication rates. CONCLUSIONS: Rate of publication in indexed journals, of papers derived from postgraduate theses is 30%. In this study we were unable to identify factors that promote publication.